2012
DOI: 10.1007/s00214-012-1179-x
|View full text |Cite|
|
Sign up to set email alerts
|

Improving the study of proton transfers between amino acid side chains in solution: choosing appropriate DFT functionals and avoiding hidden pitfalls

Abstract: Abstract:We have studied the influence of implicit solvent models, inclusion of explicit water molecules, inclusion of vibrational effects, and density functionals on the quality of the predicted pK a of small amino acid sidechain models. We found that the inclusion of vibrational effects and explicit water molecules is crucial to improve the correlation between the computed and the experimental values.However, achieving convergence of the results requires the addition of too many explicit water molecules, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The prediction was that the H-bond with lysine would be neutral in low-polarity environment, whereas the bridge is ionic with arginine in any environment. In partial disagreement with the above results, Silva et al , [ 241 ] advocated the ionic character of any salt-bridge if an Asp side chain, as the acid partner is involved. These authors emphasized the need for considering more than three explicit water molecules and accounting for vibrational contributions to the total relative free energy even when a continuum solvent model is being applied.…”
Section: Conformational Equilibriamentioning
confidence: 89%
“…The prediction was that the H-bond with lysine would be neutral in low-polarity environment, whereas the bridge is ionic with arginine in any environment. In partial disagreement with the above results, Silva et al , [ 241 ] advocated the ionic character of any salt-bridge if an Asp side chain, as the acid partner is involved. These authors emphasized the need for considering more than three explicit water molecules and accounting for vibrational contributions to the total relative free energy even when a continuum solvent model is being applied.…”
Section: Conformational Equilibriamentioning
confidence: 89%
“…Examples of QM/MM studies for which we have employed this general type of approaches include the enzymes HIV‐1 integrase, β‐hexosaminidase, β‐glycosidase, and isocitrate dehydrogenase, among others. Interestingly, we have found that the best density functionals can vary significantly from problem to problem, but common choices include MPWB1K, or M06 . In many cases, however, we have found that B3LYP still remains a safe choice, particularly when used in combination with large basis sets and with a dispersion correction .…”
Section: Types Of Qm/mm Schemesmentioning
confidence: 99%
“…The latter paper includes a discussion related to the glycine zwitterion formation and the observed contradictions between experiment and theoretical calculations. A recent study [200] deals with the problem of the proton transfers between amino acid side chains in solution.…”
Section: Zwitterionic Amino Acidsmentioning
confidence: 99%